A Novel End-to-End Biliary-to-Biliary Anastomosis Technique for Iatrogenic Bile Duct Injury of Strasberg-Bismuth E1-4 Treatment: A Retrospective Study and in vivo Assessment - Ma, Dong; Liu, Pengpeng; Lan, Jianwei; Chen, Baiyang; Gu, Yang; Li, Yun; Yue, Pengpeng; Liu, Zhisu; Guo, Deliang (Frontiers in Surgery, 2021)
Background Iatrogenic bile duct injury(IBDI) is a severe complication that have a great impact on the patients’ physical and mental quality of life, especially for patients with postoperative benign biliary stricture. Effective measures for end-to-end biliary-to-biliary anastomosis intraoperative are essential to prevent postoperative bile duct stricture, but also a challenge even to the most skilled biliary tract surgeon. Objective Postoperative benign biliary stricture is an extremely intractable complication that occurs following Iatrogenic bile duct injury. Our goal was to introduce a novel end-to-end biliary-to-biliary anastomosis technique named fish-mouth-shaped (FMS) end-to-end biliary-to-biliary reconstruction and determine the safety and effectiveness for preventing postoperative benign biliary stricture in both rats and humans. Methods 18 biliary injured patients who underwent a FMS reconstruction procedure were retrospectively analyzed. Their general information, disease of first hospitalization, operation method, classification of bile duct injury were collected. Postoperative complications were evaluated immediately perioperatively and long-term complications were followed up at the later period of at least 5 years. An IBDI animal model using 18 male rats was developed for animal-based evaluations. A bile duct diathermy injury model was used to mimic bile duct injury. The FMS group underwent FMS reconstruction procedure while the control group underwent common end-to-end biliary-to-biliary anastomosis, a sham operation group was also established. Blood samples, liver, spleen and common bile duct tissues were harvested for further assessments. Results In the retrospective study, there was no postoperative mortality and no patient developed cholangitis during the 5-years postoperation follow-up. In the study of IBDI animal models, compared with the control group, FMS reconstruction procedure reduced the occurrence of benign biliary stenosis, liver function damage and jaundice. Blood test as well as morphological and pathological observations revealed that rats in the FMS reconstruction group had better recovery than those in the control group. Conclusions FMS reconstruction procedure is a safe and efficient bile duct injury treatment method.